Issues in the National Supply Policy of Nepal - Panta, Laxmi (Economic Journal of Development Issues, 2018)
Rationality of public policy analysis emerges due to the need of understanding the nature of policies and their elements towards solving societal problems. National supply policy is formulated and implemented for the regular supply of necessary goods and services in the country. Effective implementation of the policy depends on its structure as well as on the external factors from the prevailing situation in the country. In the present article an attempt has been made to highlight the basic features of the current national supply policy of Nepal and discuss the issues related with its effective implementation. Despite several elements proposed in the policy only few have the result oriented features. Many of the elements are ambitious as well as vague. Imperfection in policy implementation witnessed during the suddenly arrived difficulties as well as at the normal time. From the discussion it has been concluded that the policy has weaknesses in its structure, basically in maintenance of hierarchy of objectives and has been facing several unsolved practical issues. Economic Journal of Development Issues Vol. 23&24 No. 1-2, (2017) Combined Issue, Page : 123-136